(untitled) (Progressive Agriculture, 2021)
Worldwide, tobacco is one of the leading causes of disability and death. Over a million of pounds of toxic chemicals are released by tobacco products. This study aims to explore the effects of tobacco toxicants on human health and environmental pollution. Four districts (Dhaka, Kushtia, Chattogram and Rangpur) were selected where most of the tobacco product grown. Total 468 respondents were interviewed face-to-face using structured questionnaire to assess the knowledge about toxicant content in tobacco and health and environmental hazards of tobacco use. Survey results revealed that about 44.4% respondents used smoking tobacco products and 38.5% used smokeless tobacco, while only 17.1% used both. About two third (74.3%) of smoking tobacco users started smoking when they were between 15 to 24 years old and majority (61.6%) of smokeless tobacco users started tobacco when they were between 30 to 35 years above. Tobacco product has large impacts on health of young smokers. Smokers are suffering from various acute and chronic diseases. Among the respondents, 38% indicated that they were suffering from hypertension. The second most affected disease was COPD/Asthma (31.6%), while cancer was the least suffering disease (0.4%). Majority of the respondents were not aware about the presence of toxicants (i.e. nicotine, tar and metals) in tobacco products. However, 85.1% tobacco users had an idea about environmental pollution. There is a lack of knowledge among the survey respondents about toxicants in tobacco products that are linked to health hazards and environmental pollution. These results are important in strengthening existing policy considering adverse health effects of toxicants examined. Progressive Agriculture 31 (3): 130-143, 2020